Internet censorship detected in Myanmar (Myanmar) - Voidly (2026)
CRITICAL severity censorship detected in Myanmar. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: MM-2026-0362
Keywords: censorship; MM; censorship; critical